Community Plan Making in the Face of Ethnic Conflict in Israel: Lessons for Collaborative Planning Processes. Issue 2 (3rd April 2017) - Shmueli, Deborah F.
Abstract : Problem, research strategy, and findings : I focus on community plan making in Israel in the face of ethnic conflict, examining ways in which community-level planning processes are embedded into larger decision systems and how attention to multiscale, institutional linkages and parallel processes can determine the success of collaborative planning efforts. I present a community development case about a dispute over a local Bedouin land claim in a Jewish community in northern Israel, mediated over more than a decade. My research is based on a longitudinal 12-year case study of this planning dispute. There were three phases to the plan making: facilitated strategic plan development, facilitated collaborative decision making, and direct negotiations. Community planning is inevitably a lengthy endeavor, embedded in concentric decision contexts. The first 10 years of the dispute were devoted to achieving shared agreements among community members at the table, ignoring the interfacing and partnerships with state, national, or other nonlocal stakeholders. Only in the last two years did the community finally forge these relationships and reach an understanding of the impacts that parallel processes (occurring outside of the community) would have on the local dispute, leading to a community plan and resolution. Takeaway for practice : Community planning agendas must consider the interests of all relevant stakeholders, paying attention to multiscale, nonlocal players. Planners need to maintain and understand the links to and knowledge of other ongoing planning processes to understand how they might affect the community plan-making process at hand. Ethnic conflict cannot be ignored. Continuing with the business of community planning in the face of ethnic conflict in some ways helps minimize the importance of the ethnic dispute.